3D cementitious composites printing with pretreated recycled crumb rubber: mechanical and acoustic insulation properties - Wang, Xiangyu (2024)
Cementitious materials incorporating recycled crumb rubber have become a common sustainable resolution in diverse building environments to achieve various functions in terms of lightweight, ductility, as well as energy absorption. This study explored the 3D printed rubberised cementitious composites (3DPRC) in two aspects: examining the effects of crumb rubber pretreatment conditions on compressive properties; conducting experimental and numerical analysis on the acoustic dissipation characteristics of 3DPRC. Fine crumb rubber granules (3-5 mm) replaced 10%, 20%, and 30% of river sand in the composites. Uniaxial compression tests indicated that the compressive strength of 3DPRC decreased with the increase of crumb rubber content and introduced anisotropic behaviour. Impedance tube tests were conducted to evaluate the sound absorption and insulation capabilities of 3DPRC. An optimal Noise Reduction Coefficient (NRC) of 0.35 was achieved with 30% crumb rubber. The sound insulation properties depend strongly on the mass density and porosity of the 3DPRC. Additionally, it is proved that the volume of built-in air gap has positive effects on both sound absorption and insulation properties. The results from Finite Element Method (FEM) numerical simulations correlated well with experimental data, proving the efficiency of the simulation and validating the experimental results.